2020
DOI: 10.1177/2050313x20940430
|View full text |Cite
|
Sign up to set email alerts
|

Pyoderma gangrenosum treated with secukinumab: A case report

Abstract: Pyoderma gangrenosum is a challenging disease to manage, due in part to the lack of approved treatment therapies. Recently, the emergence of biologic agents has expanded treatment options, with tumour necrosis factor alpha inhibitors being the best supported in the literature. In our report, we present a 50-year-old female with pyoderma gangrenosum who was successfully treated with the anti-interleukin-17 biologic agent, secukinumab, after failing other systemic therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 16 publications
0
22
0
Order By: Relevance
“…Anti-tumor necrosis alpha inhibitors were also found to facilitate a faster wound healing of PG lesions than steroids alone [27]. Additional therapeutic options used in the successful treatment of PG target other cytokines in the inflammatory cascade, including IL-12/IL-23 (ustekinumab) [28], IL-17 (secukinumab) [29], IL-1β (canakinumab) [30], IL-1 Receptor I (anakinra) [31], IL-6 (tocilizumab) [19], JAK1,2 and 3 (tofacitinib and ruxolitinib) [32,33], and phosphodiesterase 4 (PDE4) (apremilast) [34]. There is also evidence that intravenous immune globulin (IVIG) can be used successfully as an adjuvant treatment for PG [35][36][37].…”
Section: Treatmentmentioning
confidence: 99%
“…Anti-tumor necrosis alpha inhibitors were also found to facilitate a faster wound healing of PG lesions than steroids alone [27]. Additional therapeutic options used in the successful treatment of PG target other cytokines in the inflammatory cascade, including IL-12/IL-23 (ustekinumab) [28], IL-17 (secukinumab) [29], IL-1β (canakinumab) [30], IL-1 Receptor I (anakinra) [31], IL-6 (tocilizumab) [19], JAK1,2 and 3 (tofacitinib and ruxolitinib) [32,33], and phosphodiesterase 4 (PDE4) (apremilast) [34]. There is also evidence that intravenous immune globulin (IVIG) can be used successfully as an adjuvant treatment for PG [35][36][37].…”
Section: Treatmentmentioning
confidence: 99%
“…It has been reported that PG responds well to biologics against IL-1β, 13 IL-12, 14 IL-17, 15 IL-23, 16 IL-1 receptor, 17 IL-6 receptor 18 and most commonly TNF. 19 The T helper (Th)17/TNF-α axis leading to neutrophil infiltration has been shown in the pathogenetic basis of psoriasis, 20 PPP 8 and PG.…”
Section: Discussionmentioning
confidence: 99%
“…However, uncontrolled IL-17A activity has a negative impact on the wound-healing process by intensifying the inflammatory response via pro-inflammatory cytokines’ production as evident in chronic wounds. Most importantly, case reports of the use of Ustekinumab (anti-IL23 monoclonal antibody) and Secukinumab or Ixekizumab (anti-IL17A monoclonal antibody) treatments in pyoderma gangrenosum (a skin ulceration condition as a comorbidity of other chronic inflammatory diseases) show improved wound healing without compromising keratinocyte function [ 128 , 129 , 130 , 131 ].…”
Section: Strategies To Modulate Wound Inflammation and Macrophage Act...mentioning
confidence: 99%